Direct Electron Transfer of Cytochrome c on ZnO Nanoparticles Modified Carbon Paste Electrode. (25th March 2012) - Negahdary, Masoud; Rezaei-Zarchi, Saeed; Rousta, Neda; Samei Pour, Soheila
Abstract : The direct electrochemistry of cytochrome c (cyt c) immobilized on a modified carbon paste electrode (CPE) was described. The electrode was modified with ZnO nanoparticles. Direct electrochemistry of cytochrome c in this paste electrode was easily achieved, and a pair of well-defined quasireversible redox peaks of a heme Fe (III)/Fe(II) couple appeared with a formal potential ( E 0 ) of −0.303 V (versus SCE) in pH 7.0 phosphate buffer solution (PBS). The fabricated modified bioelectrode showed good electrocatalytic ability for reduction of H2 O2 . The preparation process of the proposed biosensor was convenient, and the resulting biosensor showed high sensitivity, low detection limit, and good stability.